Investigating the cholesterol-independent (pleiotropic) effects of selected hypolipidaemic agents in functional and dysfunctional endothelial cells - Westcott, Corli (Stellenbosch : Stellenbosch University, 2015)
Thesis (DScMedSc)--Stellenbosch University, 2015.